Yogic Practice Improves Neuromuscular Coordination in Sedentary Middle-Aged Women: An Experimental Study - Asit Mahara; Md Nasim Reza; Aminur Rahaman; Sentu Mitra; Md. Arman Gazi; Md. Hamidur Rahman (Physical Education Theory and Methodology, 2025)
Background.  Kinesthetic perception, static balance, and coupling ability are essential components of motor coordination, particularly in middle-aged women leading sedentary lifestyles. Yogic practice is widely recognized for its benefits in enhancing physical and neuromuscular functions, but its specific impact on these variables remains underexplored.